Load case selection guideline for combined modal finite element approach for static aeroelastic deformations of rectangular HAR wing models - Chandrasegaran, Tinesh (2020)
High aspect ratio (HAR) and flexible wing models have multiple benefits. However, due to the nonlinear properties of this type of structure, the linear solution of static aeroelastic response is not sufficient to analyse the wing characteristics. Thus, making the option become more and more undesirable due to the complexity of the conventional finite element (FE) nonlinear analysis. To improve the computational efficiency of the nonlinear analysis of the HAR and flexible wing models, the Combined Modal Finite Element approach is used to characterize the nonlinear properties of the HAR wing model by the development of nonlinear reduced order models (NROM). However, till time no set of clear guidelines on the production of load cases to develop the NROM using the CMFE approach. Therefore, the research proposes a load case selection technique to develop the NROMs and investigates the possibility of predicting the nonlinear static aeroelastic response by prescribing eigenmode based load cases. For the conduct of the study in a systematic manner, the programming routine was developed and coupled with the finite element solver. The selection guideline starts with the selection of the normal modes with the most significant contribution. With the modes selected, the loading profiles were prescribed and the load cases were developed with the maximum force range criteria set. The load cases are then with the use of CMFE approach are utilized to develop the NROM to predict the nonlinear static aeroelastic deformations. The predicted nonlinear static aeroelastic response are verified with the conventional nonlinear finite element analysis and compared in terms of mean error and standard deviation. The load cases developed based on the load case selection technique is able to produce highly accurate NROMs. The study also concludes the possibility of using eigenmode based load cases to predict the nonlinear static aeroelastic response is encouraging. The NROM developed based on the eigenvector load case is a viable option since the overall results show good agreement with the nonlinear deformations obtained from the FE analysis. It is also suggested that the NROM to be developed with individual based bending and torsional load cases since these show a more accurate result than the combined bending and torsional load case. From the results, it is concluded the accuracy of the NROM is up to 97.5% of the maximum bending deflection of the wing model whereas for the twist deflection the accuracy is up to 99%. With the availability of a detailed guideline for the load case selection and the suggestion of using eigenmode based load cases, enables researchers to explore more into the option of development NROMs using the CMFE approach. Hence, this provides a more desirable alternative solution in comparison to the more complex and tedious approach of nonlinear FE analysis approach in a case of static aeroelastic deformation of high aspect ratio and highly flexible wing model.